(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the complex transformation and trajectory of Soviet religious policy in the Fergana Valley between 1946 and 1991. Following the tactical concessions made by the Soviet state during World War II, the post-war period was characterized by alternating waves of intense administrative restrictions and ideological containment. Utilizing a multidisciplinary approach that combines historical objectivity, chronological segmentation, and qualitative content analysis of declassified documents from the National Archive of Uzbekistan, this study analyzes the structural tension between the state-sanctioned “official” Islamic institutions (under SADUM) and the resilient network of “clandestine” or parallel Islam. The research reveals that despite aggressive antireligious campaigns, particularly during the Khrushchev era, the traditional socioeconomic fabric of the Fergana Valley facilitated the survival of underground religious schools (hujras), informal spiritual leaders, and Sufi networks. These covert structures successfully preserved the local cultural-religious identity and maintained the continuity of Islamic knowledge across generations. Ultimately, the article argues that the institutional suppression and artificial spiritual vacuum imposed by the totalitarian state inadvertently laid the groundwork for the rapid politicization of Islam and the religious revival that emerged in the region during Perestroika and immediately followed the collapse of the Soviet Union in 1991.